Complications of Thyroid Surgery (Medical Forum Monthly, 2024)
Objectives: To determine the percentage of complications in thyroid surgery & compare these complications with the other national & international studies. Study Design: A descriptive study. Place and Duration of Study: The study was conducted in the department of Surgery,Foundation University Medical College and Fauji Foundation Hospital Rawalpindi from 1stJanuary2009 to 31stDecember 2009. Patients and Methods: 192 patients above the age of 14 who consented were included in the study. General physical & loco regional examination was done in OPD. Thyroid function tests (T3, T4, and TSH) were done in all the patients besides other routine investigations. FNAC & thyroid scan was done in only selected patients. Anemia, hypertension& other comorbid condition, if present, were corrected & assessed by anesthetist in the pre admission clinic. Onlyeuthyroidpatients, both clinically & biochemically & fit for general anesthesia were admitted for operation. Subsequently all the patients were subjected for surgery& the specimens were sent for histopathology after visual examination. Pre as well as per operative findings were recorded on a specially designed proforma. The data were then entered in the computer for analysis & conclusions were drawn Results: Total of 192 patients operated for benign thyroid disease in year 2009. Age ranges between 14 to 80 with 120 patients below the age of 40. Out of 192 patients, only 6 were males.90 patients were operated for pressure symptoms, 78 for cosmetic reasons & 24 for toxic symptoms. Subtotal thyroidectomy was done in 132 patients while 24 patients ended up with near total & 36 were candidates for lobectomy. 6 patients had symptoms ofRLN damage while 24 develop parathyroid insufficiency post operatively. All these patients managed conservatively & discharge on 2nd or 3rd post op day. They regain normal voice& normal serum calcium levels by the end of 3 months. Conclusion: Subtotal thyroidectomy is one of the commonest procedure done by the surgeons of Rawalpindi Islamabad region. Maximum effort should be done to optimize the patients preoperatively. If patients are euthyroid& assessed carefully for anesthesia fitness before operation, chances of per or post- operative complications are negligible.